Comparing satellite SAR and wind farm wake models. (June 2015) - Hasager, C B; Vincent, P; Husson, R; Mouche, A; Badger, M; Peña, A; Volker, P; Badger, J; Di Bella, A; Palomares, A; Cantero, E; Correia, P M F
Abstract: The aim of the paper is to present offshore wind farm wake observed from satellite Synthetic Aperture Radar (SAR) wind fields from RADARSAT-1/-2 and Envisat and to compare these wakes qualitatively to wind farm wake model results. From some satellite SAR wind maps very long wakes are observed. These extend several tens of kilometres downwind e.g. 70 km. Other SAR wind maps show near-field fine scale details of wake behind rows of turbines. The satellite SAR wind farm wake cases are modelled by different wind farm wake models including the PARK microscale model, the Weather Research and Forecasting (WRF) model in high resolution and WRF with coupled microscale parametrization.